Nilai-Nilai Pendidikan Islam dalam Membentuk Budaya Religius di SMA Negeri 1 Genteng Tahun Pelajaran 2017/2018 - Ahmad Aziz Fanani; Imam Mashuri; Dina Istiningrum (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2019)
Today the need of education is increasingly high, but it is inversely proportional to the condition of education that is increasingly regressive. This happened because of the development of science, knowledge, and technology (modernism) which had a negative impact on moral decadence. Because of this threat, Islamic education as a branch of aespecially scientific discipline is expected to be a solution to the threat. Therefore, educational institutions must be able to be pioneers in improving the character of students, namely by implementing policies or programs that lead to Islamic education. One of them has been done by a non-Islamic national standard school, namely SMA Negeri 1 Genteng, which has instilled Islamic values in the educational environment.